The Effect of Spare Part Procurement and Inventory on the Smooth Operation of Floatingcrane Vessels at PT MUTIARA JAWA - Arif Hidayat; Kuni Nela Rizki Aszahra; Didik Sulistyo (Greenation Research & Yayasan Global Resarch National, 2023)
PT Mutiara Jawa is engaged in transshipment which handles loading and unloading of coal. So that the timeliness of unloading must be considered because the company must have special attention to these activities to prioritize its efforts in providing quality loading and unloading services. Based on the data, the problems that exist discuss the procurement and supply of ship spare parts for ship operations. The purpose of this study is to find out how much influence and relationship the procurement of spare parts has on the smooth operational activities of floating crane vessels. In this study found the results of data from the influence and relationship of spare part procurement to the smooth operation of floating crane vessels.